Investigation on Vibration Characteristics in a Centrifugal Pump with Special Slope Volute - Ning Zhang; MinGuan Yang; Bo Gao; Zhong Li (Advances in Mechanical Engineering, 2015)
Vibration is one of the main problems which should be considered seriously in designing and operating a centrifugal pump. In this paper, a special slope volute was proposed to reduce vibration level of centrifugal pump. The goal of this paper was to analyze vibration characteristics of slope volute pump and provide a new method to reduce vibration energy in centrifugal pump. Experiments were carried out to obtain vibration signals at different flow rates of slope volute pump, which were compared with conventional spiral volute pump. Results show that vibration level is closely related to flow structure interior pump. At low flow rates, especially, vibration energy increases rapidly with the onset of rotating stall. Rotor-stator interaction mechanism changes when adopting slope volute. In slope volute pump, the peaks in power spectra correspond to different harmonics of f BPF at three measuring directions; however, in spiral volute pump, the predominant components always correspond to 2 f BPF . From comparison of vibration level in different frequency bands, it is found that vibration level of slope volute pump is smaller than conventional spiral volute pump. So vibration energy of centrifugal pump can be reduced effectively using slope volute.